Identification of candidate genes involved in Zika virus-induced reversible paralysis of mice - John D. Morrey; Venkatraman Siddharthan; Hong Wang; Alexandre L. R. Oliveira; Keiichiro Susuki; Rakesh Kaundal; Sara M. Freeman; Aaron J. Thomas; Naveen Duhan; Nathan G. Corry (Scientific Reports)
Abstract Zika virus (ZIKV) causes a variety of peripheral and central nervous system complications leading to neurological symptoms such as limb weakness. We used a mouse model to identify candidate genes potentially involved in causation or recovery from ZIKV-induced acute flaccid paralysis. Using Zikv and Chat chromogenic and fluorescence in situ RNA hybridization, electron microscopy, immunohistochemistry, and ZIKV RT-qPCR, we determined that some paralyzed mice had infected motor neurons, but motor neurons are not reduced in number and the infection was not present in all paralyzed mice; hence infection of motor neurons were not strongly correlated with paralysis. Consequently, paralysis was probably caused by by-stander effects. To address this, we performed bioinformatics analysis on spinal cord RNA to identify 2058 differentially expressed genes (DEGs) that were altered during paralysis and then normalized after paralysis. Of these “biphasic” DEGs, 951 were up-regulated and 1107 were down-regulated during paralysis, followed by recovery. To refine the search for candidate DEGs we used gene ontology analysis and RT-qPCR to select 3 DEGs that could be involved with the node of Ranvier function and 5 DEGs that could be involved with synaptic function. Among these, SparcL1:Sparc DEG ratios were identified to be inversely correlated with ZIKV-induced paralysis, which is consistent with the known function of SPARC protein to antagonize the synaptogenesis of SPARCL1. Ank3, Sptbn1, and Epb41l3 affecting the structures at and near the nodes of Ranvier were significantly downregulated during ZIKV-induced paralysis. The primary contribution is the identification of 8 candidate genes that may be involved in the causation or recovery of ZIKV-induced paralysis.